The Strategic Management of Islamic Boarding School Education in the Industrial Environment (Research at the At-Thohirin Islamic Boarding School, Karawang Regency - Rohman, Kholilul; Haikal, Ahmad Hilmi; Supriyatna, Dede; Nursyabani, Akbar (International Journal on Advanced Science, Education, and Religion, 2024)
The purpose of this study was to determine the educational management of the At-Thohirin Islamic Boarding School in the industrial environment of Karawang Regency, to determine the dominant factors that influence the strategic management of education applied by the At-Thohirin Islamic Boarding School kiai in the industrial environment of Karawang Regency. This research is This type of field research (field research) is qualitative in nature, namely research conducted to understand social phenomena from the perspective of the perpetrators. The strategic management model used at the At-Thohirin Islamic Boarding School consists of three stages, namely: strategy formulation, strategy implementation, and strategy evaluation. Implications of the Implementation of Strategic Management at the At-Thohirin Islamic Boarding School in an industrial environment. The implication of this research is that there are changes that come from outside the pesantren. Islamic boarding schools can be divided into three namely: (1) Traditional Islamic Boarding Schools (Salafi). (2) Modern Islamic Boarding School. (3) Industrial Salafi Islamic Boarding Schools are conservative towards the industrial environment, this must adapt to the industrial environment. Keywords: Strategic Management, Islamic Boarding School Education, Industrial Environment